2004
DOI: 10.1007/s00125-003-1265-7
|View full text |Cite
|
Sign up to set email alerts
|

Disassociation of muscle triglyceride content and insulin sensitivity after exercise training in patients with Type 2 diabetes

Abstract: Aim/hypothesis. We determined the effect of exercise training on insulin sensitivity and muscle lipids (triglyceride [TG m ] and long-chain fatty acyl CoA [LCACoA] concentration) in patients with Type 2 diabetes. Methods. Seven patients with Type 2 diabetes and six healthy control subjects who were matched for age, BMI, % body fat and VO 2 peak participated in a 3 days per week training program for 8 weeks. Insulin sensitivity was determined pre-and post-training during a 120 min euglycaemic-hyperinsulinaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 41 publications
8
136
3
1
Order By: Relevance
“…Importantly, exercise increased insulin sensitivity despite the ewes in the present study gaining significant body weight between preexercise and postexercise tests. This is consistent with the fact that exercise training increases insulin sensitivity before weight is lost in humans (6).…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, exercise increased insulin sensitivity despite the ewes in the present study gaining significant body weight between preexercise and postexercise tests. This is consistent with the fact that exercise training increases insulin sensitivity before weight is lost in humans (6).…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, physical activity or exercise training has been shown to reduce visceral fat [33], improve skeletal muscle insulin sensitivity [37,38] and increase the oxidative capacity of skeletal muscle, which correlates with insulin sensitivity [39], and also leads to increased/modified fat oxidation, which is most likely to prevent lipid-mediated insulin resistance [40].…”
Section: Discussionmentioning
confidence: 99%
“…ES for each of the controlled trials was interpreted according to the method of Cohen [16]. from 18 studies including 3 randomized controlled trials reported in 9 publications [17][18][19][20][21][22][23][24][25] (2 trials reported in 8 publications with resistance training [17][18][19][20][21][22][23][24] and 1 with aerobic training [25]), 2 non-randomized controlled trials [26,27] (with aerobic training [26,27]) and 13 uncontrolled trials reported in 15 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (11 trials reported in 13 publications with aerobic training [28,[30][31][32][33][34][35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized controlled trials and non-randomized controlled trials, all studies consisted of mixed gender cohorts [17][18][19][20][21][22][23][24][25][26][27]; in the uncontrolled trials, five studies published in six papers were in male cohorts [31,32,34,37,38,42], seven studies published in eight papers were in mixed cohorts [28][29][30]33,35,36,39,41] and one study did not report gender [40].…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation